PERBANDINGAN MOTIF DAN MAKNA SIMBOLIS BATIK TIONGKOK DAN BATIK JAWA TENGAH - Miftah Khoirun Nisa; Muhammad Fauzan Ridho Athallah; Shalfa Salsabila (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study examines the comparative characteristics of motifs and symbolic meanings in Chinese batik (la ran) and Indonesian batik, particularly from Central Java, using a qualitative library research approach. Although both traditions employ similar wax-resist dyeing techniques, their motif development is shaped by different historical, philosophical, and cultural contexts. The findings indicate that Chinese batik emphasizes representational motifs such as dragons, phoenixes, and plum blossoms, symbolizing cosmic power, harmony, fortune, and resilience, influenced by Confucianism, Taoism, and Chinese mythology. In contrast, Central Javanese batik highlights geometric and stylized motifs such as parang, kawung, and truntum, reflecting moral values, self-restraint, spirituality, and social harmony. The comparative analysis reveals clear differences in visual orientation, symbolic interpretation, and social function between the two traditions. This study contributes to a deeper understanding of Asian textile arts and cross-cultural batik symbolism.